Sujetos en tránsito: las voces de una lengua exiliada. Análisis de textos de Juan Martini y de Junot Díaz - Tozzi, Liliana (Confluenze. Rivista di Studi Iberoamericani, 2009)
In this article, I try to search in a comparative way the relationship between migration and literature in La construcción del héroe (1989), by the argentine writer Juan Martini, and Los boys (1996), by the Dominican Junot Díaz. In both novels, the migrancy marks the characters’ life and installs in the texts the intercultural tensions that the displacement generates. The heroes are fastened in traffic, which mobile mansion escapes of the geography to be constituted as an area in permanent mutation. Across the analysis I will try to establish in a contrastive way the characteristics of these migrants subjects, in relation with the identity and the use of the language. En este trabajo me propongo indagar, comparativamente, la relación entre migración y literatura en La construcción del héroe (1989) del escritor argentino Juan Martini y Los boys (1996) del dominicano Junot Díaz. En ambos relatos, la migrancia marca la vida de los personajes e instala en los textos las tensiones interculturales que genera el desplazamiento. Los héroes son sujetos en tránsito, cuya morada móvil fuga de la geografía para constituirse como un ámbito en permanente mutación. A través del análisis intentaré establecer de manera contrastiva las características de estos sujetos migrantes, en relación con la identidad y el uso de la lengua.